Stenoptilia pneumonanthes ... - Ustjuzhanin, P. Ya.; Kovtunovich, V. N.; Saldaitis, A.; Streltzov, A. N. (Zenodo, 2021)
Stenoptilia pneumonanthes (Buttner, 1880) MATERIAL EXAMINED. 3 ♂♂, China, NW Sichuan, near Maniganggo, h≈ 3860m, 31°47´S, 99°23´E, 30.vi.2009, J. Butvila & A. Saldaitis leg. DISTRIBUTION.Europe, European part of Russia, South Siberia, Yakutia, Kazakhstan, China (Shanxi, Xinjiang, Sichuan). ... : Published as part of Ustjuzhanin, P. Ya., Kovtunovich, V. N., Saldaitis, A. & Streltzov, A. N., 2021, New species of plume moths (Lepidoptera: Pterophoridae) from China, Sichuan Province, pp. 323-327 in Russian Entomological Journal 30 (3) on page 326, DOI: 10.15298/rusentj.30.3.10, http://zenodo.org/record/13178983 ...